A nickel-iron co-doped manganese-based Prussian blue positive electrode material and its preparation method and application
By designing a non-uniform co-doped structure of nickel iron in the Mn-PB positive electrode material, the distribution of transition metal ions is regulated, and the stability problem caused by the Jahn-Teller effect of Mn3+ is solved, and higher structural stability and electricity are achieved Chemical properties.
Patent Information
- Application Number
- CN202410410750.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-08
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-04-08
AI Technical Summary
The electrochemical performance stability of Mn-PB positive electrode material is restricted by the Jahn-Teller effect of Mn3+, which affects its cyclic performance.
By designing a manganese-based Prussian blue positive electrode material with non-uniform co-doped nickel iron, nickel is enriched outside the particles, manganese is enriched inside the particles, and iron is uniformly distributed throughout the particles, regulating the types and distribution of transition metal ions, improving The structural stability of the material and the diffusion dynamics of the sodium ion.
The structural stability and electrochemical properties of the positive electrode material are significantly improved, the discharge specific capacity and cyclic stability are enhanced, and the rate performance is improved.
Smart Images

Figure CN118299556B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of cathode materials, and more specifically, to a nickel-iron co-doped manganese-based Prussian blue cathode material, its preparation method and application. Background Art
[0002] Sodium-ion batteries are considered to be one of the most suitable secondary battery systems for energy storage due to the abundant sodium resources and low cost. Prussian blue materials (PBAs) (chemical formula: Na x M1[M2(CN)6] 1-y □ y ·nH2O, where 0 < x < 2, 0 < y < 1, M1 / M2: transition metal ions, □: [F(CN)6] vacancy) are considered to be one of the cathode materials that urgently need to be mass-produced due to advantages such as adjustable elemental composition and open pore gaps. Among the currently discovered PBA materials, sodium manganese ferrocyanide (Mn-PB) with a two-electron redox reaction exhibits the highest theoretical specific capacity, and can even be comparable to LiFePO4 (the cathode material of typical LIBs), and is used for high-energy density energy storage devices (≈450 Wh kg -1 ). However, the stable display of the electrochemical performance of Mn-PB is often restricted by the inevitable Jahn-Teller effect of Mn 3+ .
[0003] Therefore, it is particularly important to explore effective modification measures to stabilize the structure of Mn-PB for improving the battery cycle performance. Summary of the Invention
[0004] Based on the above technical problems existing in the prior art, the present invention provides a nickel-iron non-uniformly co-doped manganese-based Prussian blue cathode material. By designing and modifying the types and distributions of transition metal elements in the cathode material, the present invention not only effectively improves the structural stability of the manganese-based Prussian blue cathode material, but also improves the sodium-ion diffusion kinetics of the cathode material and enhances the electrochemical performance of the material.
[0005] To achieve the above object, the technical solution of the present invention is as follows:
[0006] A nickel-iron non-uniformly co-doped manganese-based Prussian blue cathode material, with the molecular formula: Na2Ni a Fe b Mn c [Fe(CN)6], where 0.1 ≤ a ≤ 0.2, 0.4 ≤ b ≤ 0.45, 0.4 ≤ c ≤ 0.45 and a + b + c = 1; in its single crystal particles, nickel is enriched on the outside of the particles, manganese is enriched inside the particles, and iron is evenly distributed throughout the particles.
[0007] In some embodiments, in a single crystal particle, the molar ratio of nickel, iron and manganese is 1-2:4-4.5:4-4.5; preferably, the molar ratio of nickel, iron and manganese is 1:4.5:4.5 or 2:4:4.
[0008] The present invention also provides a method for preparing the nickel-iron co-doped manganese-based Prussian blue positive electrode material of any of the above embodiments, the method comprising the following steps:
[0009] S1, weighing a nickel source, an iron source, a manganese source, ascorbic acid and a complexing agent, and dissolving them in a first solvent to obtain a solution A;
[0010] S2, weighing sodium ferrocyanide, and dissolving it in the second solvent to obtain solution B;
[0011] S3. Under a protective gas atmosphere, slowly drop the solution B into the solution A, react at room temperature, and then separate the solid and the liquid to obtain the positive electrode material.
[0012] In some embodiments, in step S3, the speed of adding solution B dropwise into solution A is 1-10 ml / min.
[0013] In some embodiments, the nickel source includes at least one of nickel chloride, nickel nitrate, nickel sulfate, nickel carbonate, nickel oxalate, nickel acetate, and nickel citrate.
[0014] In some embodiments, the iron source includes at least one of ferrous chloride, ferrous nitrate, ferrous sulfate, ferrous carbonate, ferrous oxalate, ferrous acetate, and ferrous citrate.
[0015] In some embodiments, the manganese source includes at least one of manganese chloride, manganese nitrate, manganese sulfate, manganese carbonate, manganese oxalate, manganese acetate, and manganese citrate.
[0016] In some embodiments, the complexing agent includes at least one of sodium citrate, carboxymethyl cellulose, disodium edetate, and sodium tartrate.
[0017] In some embodiments, the protective gas atmosphere is one of argon atmosphere, helium atmosphere, and nitrogen atmosphere.
[0018] In some embodiments, the first solvent is deionized water; and the second solvent is deionized water.
[0019] In some embodiments, the preparation method comprises the following steps:
[0020] S1, weighing a nickel source, an iron source, a manganese source, ascorbic acid and a complexing agent, and dissolving them in a first solvent to obtain a solution A;
[0021] S2, weighing sodium ferrocyanide, and dissolving it in the second solvent to obtain solution B;
[0022] S3, under a protective atmosphere, slowly dropwise adding the solution B into the solution A, reacting at room temperature, and then separating the solid and the liquid to obtain a solid product;
[0023] S4, washing the solid product with water and / or ethanol, and then drying to obtain the positive electrode material.
[0024] In some embodiments, in step S1, the raw material is added to the first solvent and then stirred sufficiently to obtain solution A; wherein the stirring rate is 200-1000 rpm.
[0025] In some embodiments, in step S2, the raw material is added to the second solvent and then stirred sufficiently to obtain solution B; wherein the stirring rate is 200-1000 rpm.
[0026] In some embodiments, in step S4, drying is performed at 80-160°C.
[0027] The present invention also provides an electrode material, wherein the positive electrode material comprises the positive electrode material of any of the above embodiments or the positive electrode material obtained by the preparation method of any of the above embodiments.
[0028] The present invention also provides an electrode, comprising the above-mentioned electrode material.
[0029] The present invention also provides an electrochemical energy storage device, comprising the above-mentioned electrode.
[0030] Specifically, the electrochemical energy storage device includes a sodium ion battery, a sodium ion capacitor, and the like.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] The present invention regulates the types of transition metal ions and their distribution positions inside the manganese-based Prussian blue material, so that the obtained positive electrode material exhibits excellent electrochemical performance. Among them, the doping of nickel and iron with a radius similar to that of manganese atoms can change the charge distribution in the positive electrode skeleton, enhance the reaction activity of low-spin iron, and improve the discharge specific capacity of the positive electrode material; in addition, the uniformly distributed iron can alleviate the Jahn-Teller stress enrichment of the positive electrode material; the nickel enriched on the outside can inhibit the release of Jahn-Teller stress, isolate the direct contact between the electrolyte and manganese, inhibit the loss of active components, and significantly improve the cycle stability of the positive electrode material; at the same time, the special element distribution improves the sodium ion conductivity of the positive electrode material, which helps to improve the rate performance of the positive electrode material.
[0033] Manganese-based Prussian blue non-uniformly co-doped with nickel and iron achieves multi-atom skeleton doping and multi-atom differential enrichment in one step, significantly improving the sodium storage capacity and mass transfer rate of the positive electrode material and enhancing the structural stability of the positive electrode material.
[0034] The preparation method provided by the present invention can directly obtain a positive electrode material non-uniformly co-doped with multiple elements by directly changing the ion composition of the reaction solution. The preparation method is simple and suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 The XRD pattern of the nickel-iron non-uniformly co-doped manganese-based Prussian blue positive electrode material obtained in Example 1;
[0036] Figure 2 The discharge specific capacity of the positive electrode material obtained in Example 1 at a voltage of 2.0-4.2V and a current density of 0.1C;
[0037] Figure 3 The cycle curve of the positive electrode material obtained in Example 1 at a voltage of 2.0-4.2V and a current density of 5.0C;
[0038] Figure 4 This is the XRD pattern of the manganese-based Prussian blue positive electrode material obtained in Comparative Example 1;
[0039] Figure 5 The discharge specific capacity of the positive electrode material obtained in Comparative Example 1 at a voltage of 2.0-4.2V and a current density of 0.1C;
[0040] Figure 6 This is a cycle curve diagram of the positive electrode material obtained in Comparative Example 1 at a voltage of 2.0-4.2V and a current density of 5.0C. DETAILED DESCRIPTION
[0041] Many specific details are set forth in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar modifications without violating the connotation of the present invention, so the present invention is not limited to the specific implementation disclosed below.
[0042] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0043] Example 1
[0044] A nickel-iron non-uniformly co-doped manganese-based Prussian blue cathode material Na2Ni 0.1 Fe0.45 Mn 0.45 The preparation method of [Fe(CN)6] comprises the following steps:
[0045] S1. Add 0.1316 g of nickel sulfate hexahydrate, 0.3841 g of manganese sulfate monohydrate, 0.6319 g of ferrous sulfate heptahydrate, 0.4000 g of ascorbic acid and 4.000 g of sodium citrate to 200 mL of deionized water, stir at 400 rpm at room temperature for 60 min to obtain solution A.
[0046] S2, add 2.4313 g of sodium ferrocyanide into 200 mL of deionized water, stir at 400 rpm at room temperature, and stir for 60 min to obtain solution B;
[0047] S3. Under an argon atmosphere, solution B was slowly added dropwise to solution A at a rate of 3 ml / min, and the reaction was continued with stirring at room temperature for 12 h. After the reaction was completed, the solution was allowed to stand for 12 h, and the solid-liquid separation was performed to obtain the product;
[0048] S4. Wash the product with deionized water and ethanol for 3-4 times, and dry it in a vacuum oven at 120° C. for 24 hours to obtain the positive electrode material.
[0049] The obtained positive electrode material was characterized, and its XRD test results were as follows Figure 1 As shown. Figure 1 The positive electrode material obtained by the method of this embodiment is a cubic phase nickel-iron non-uniformly doped manganese-based Prussian blue positive electrode material.
[0050] The positive electrode material obtained in this example was subjected to electrochemical performance testing. The test results are as follows: Figure 2-3 shown.
[0051] like Figure 2 The positive electrode material obtained in this embodiment has a discharge specific capacity of 131.0 mAh / g at a voltage of 2.0-4.2 V and a current density of 0.1 C.
[0052] like Figure 3 The positive electrode material obtained in this embodiment has a discharge capacity retention rate of 85.2% after 1000 cycles at a voltage of 2.0-4.2V and a current density of 5C.
[0053] Comparative Example 1
[0054] A method for preparing a manganese-based Prussian blue positive electrode material Na2Mn[Fe(CN)6] comprises the following steps:
[0055] S1. Add 0.8536 g of manganese sulfate monohydrate and 4.000 g of sodium citrate into 200 mL of deionized water, stir at 400 rpm at room temperature for 60 min to obtain solution A.
[0056] S2, add 2.4313 g of sodium ferrocyanide into 200 mL of deionized water, stir at 400 rpm at room temperature, and stir for 60 min to obtain solution B;
[0057] S3. Under an argon atmosphere, solution B was slowly added dropwise to solution A at a rate of 3 ml / min, and the reaction was continued with stirring at room temperature for 12 h. After the reaction was completed, the solution was allowed to stand for 12 h, and the solid-liquid separation was performed to obtain the product;
[0058] S4. Wash the product with deionized water and ethanol for 3-4 times, and dry it in a vacuum oven at 120° C. for 24 hours to obtain the positive electrode material.
[0059] The obtained positive electrode material was characterized, and its XRD test results were as follows Figure 4 As shown. Figure 4 The positive electrode material obtained by the method of this comparative example is a cubic manganese-based Prussian blue positive electrode material.
[0060] The positive electrode material obtained in this comparative example was subjected to electrochemical performance testing. The test results are as follows: Figure 5-6 shown.
[0061] like Figure 5 The positive electrode material obtained in this comparative example has a discharge specific capacity of 114.6 mAh / g at a voltage of 2.0-4.2 V and a current density of 0.1 C.
[0062] like Figure 6 The positive electrode material obtained in this comparative example has a discharge capacity retention rate of 23.3% after 1000 cycles at a voltage of 2.0-4.2V and a current density of 5C.
[0063] Comparative Example 2
[0064] A nickel-inhomogeneously doped manganese-based Prussian blue cathode material Na2Ni 0.1 Mn 0.9 The preparation method of [Fe(CN)6] comprises the following steps:
[0065] S1. Add 0.1316 g of nickel sulfate hexahydrate, 0.7683 g of manganese sulfate monohydrate and 4.000 g of sodium citrate into 200 mL of deionized water, stir at 400 rpm at room temperature for 60 min to obtain solution A.
[0066] S2, add 2.4313 g of sodium ferrocyanide into 200 mL of deionized water, stir at 400 rpm at room temperature, and stir for 60 min to obtain solution B;
[0067] S3. Under an argon atmosphere, solution B was slowly added dropwise to solution A at a rate of 3 ml / min, and the reaction was continued with stirring at room temperature for 12 h. After the reaction was completed, the solution was allowed to stand for 12 h, and the solid-liquid separation was performed to obtain the product;
[0068] S4. Wash the reaction product with deionized water and ethanol for 3-4 times, and dry it in a vacuum oven at 120° C. for 24 hours to obtain the positive electrode material.
[0069] After testing, the positive electrode material obtained in this comparative example has a discharge specific capacity of 101.1 mAh / g at a voltage of 2.0-4.2 V and a current density of 0.1 C.
[0070] The positive electrode material obtained in this comparative example has a discharge capacity retention rate of 64.9% after 1000 cycles at a voltage of 2.0-4.2V and a current density of 5.0C.
[0071] Comparative Example 3
[0072] A manganese-based Prussian blue cathode material Na2Fe doped with iron 0.5 Mn 0.5 The preparation method of [Fe(CN)6] comprises the following steps:
[0073] S1. Add 0.4268 g of manganese sulfate monohydrate, 0.7021 g of ferrous sulfate heptahydrate, 0.4000 g of ascorbic acid and 4.000 g of sodium citrate into 200 mL of deionized water, stir at 400 rpm at room temperature for 60 min to obtain solution A.
[0074] S2, add 2.4313 g of sodium ferrocyanide into 200 mL of deionized water, stir at 400 rpm at room temperature, and stir for 60 min to obtain solution B;
[0075] S3. Under an argon atmosphere, solution B was slowly added dropwise to solution A at a rate of 3 ml / min, and the reaction was continued with stirring at room temperature for 12 h. After the reaction was completed, the reaction was allowed to stand for 12 h to obtain the product;
[0076] S4. Wash the reaction product with deionized water and ethanol for 3-4 times, and dry it in a vacuum oven at 120° C. for 24 hours to obtain the positive electrode material.
[0077] After testing, the positive electrode material obtained in this comparative example has a discharge specific capacity of 123.4 mAh / g at a voltage of 2.0-4.2 V and a current density of 0.1 C.
[0078] The positive electrode material obtained in this comparative example has a discharge capacity retention rate of 59.1% after 1000 cycles at a voltage of 2.0-4.2V and a current density of 5.0C.
[0079] Example 2
[0080] A nickel-iron non-uniformly co-doped manganese-based Prussian blue cathode material Na2Ni 0.2 Fe 0.4 Mn 0.4 The preparation method of [Fe(CN)6] comprises the following steps:
[0081] S1. Add 0.2631 g of nickel sulfate hexahydrate, 0.3415 g of manganese sulfate monohydrate, 0.5617 g of ferrous sulfate heptahydrate, 0.4000 g of ascorbic acid and 4.000 g of sodium citrate to 200 mL of deionized water, stir at 400 rpm at room temperature for 60 min to obtain solution A.
[0082] S2, add 2.4313 g of sodium ferrocyanide into 200 mL of deionized water, stir at 400 rpm at room temperature, and stir for 60 min to obtain solution B;
[0083] S3. Under an argon atmosphere, solution B was slowly added dropwise to solution A at a rate of 3 ml / min, and the reaction was continued with stirring at room temperature for 12 h. After the reaction was completed, the solution was allowed to stand for 12 h, and the solid-liquid separation was performed to obtain the product;
[0084] S4. Wash the product with deionized water and ethanol for 3-4 times, and dry it in a vacuum oven at 120° C. for 24 hours to obtain the positive electrode material.
[0085] After testing, the positive electrode material obtained in this embodiment has a discharge specific capacity of 101.5 mAh / g at a voltage of 2.0-4.2 V and a current density of 0.1 C.
[0086] The positive electrode material obtained in this embodiment has a discharge capacity retention rate of 86.2% after 1000 cycles at a voltage of 2.0-4.2V and a current density of 5C.
[0087] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0088] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A nickel-iron co-doped manganese-based Prussian blue positive electrode material, characterized in that: The molecular formula is: Na2Ni a Fe b Mn c [Fe(CN)6], wherein 0.1≤a≤0.2, 0.4≤b≤0.45, 0.4≤c≤0.45 and a+b+c=1; in a single crystal particle, nickel is concentrated outside the particle, manganese is concentrated inside the particle, and iron is evenly distributed throughout the particle; The preparation method comprises the following steps: S1. Weigh a nickel source, an iron source, a manganese source, ascorbic acid and a complexing agent, and dissolve them in water to obtain a solution A; S2. Weigh sodium ferrocyanide and dissolve it in water to obtain solution B; S3, under a protective gas atmosphere, slowly dropwise adding the solution B into the solution A, reacting at room temperature, and then separating the solid and the liquid to obtain the positive electrode material; In step S3, the speed of adding solution B dropwise into solution A is 1-10 ml / min.
2. The nickel-iron co-doped manganese-based Prussian blue positive electrode material according to claim 1, characterized in that: In a single crystal particle, the molar ratio of nickel, iron and manganese is 1-2:4-4.5:4-4.
5.
3. The method for preparing the nickel-iron co-doped manganese-based Prussian blue positive electrode material according to claim 1 or 2, characterized in that: The following steps are involved: S1. Weigh a nickel source, an iron source, a manganese source, ascorbic acid and a complexing agent, and dissolve them in water to obtain a solution A; S2. Weigh sodium ferrocyanide and dissolve it in water to obtain solution B; S3. Under a protective gas atmosphere, slowly drop the solution B into the solution A, react at room temperature, and then separate the solid and the liquid to obtain the positive electrode material.
4. The method for preparing the nickel-iron co-doped manganese-based Prussian blue positive electrode material according to claim 3, characterized in that: The nickel source includes at least one of nickel chloride, nickel nitrate, nickel sulfate, nickel carbonate, nickel oxalate, nickel acetate, and nickel citrate; and / or, the iron source includes at least one of ferrous chloride, ferrous nitrate, ferrous sulfate, ferrous carbonate, ferrous oxalate, ferrous acetate, and ferrous citrate; and / or, the manganese source includes at least one of manganese chloride, manganese nitrate, manganese sulfate, manganese carbonate, manganese oxalate, manganese acetate, and manganese citrate.
5. The method for preparing the nickel-iron co-doped manganese-based Prussian blue positive electrode material according to claim 3, characterized in that: The complexing agent includes at least one of sodium citrate, carboxymethyl cellulose, disodium ethylenediaminetetraacetate and sodium tartrate.
6. The method for preparing the nickel-iron co-doped manganese-based Prussian blue positive electrode material according to any one of claims 3 to 5, characterized in that: The following steps are involved: S1, weighing a nickel source, an iron source, a manganese source, ascorbic acid and a complexing agent, and dissolving them in a first solvent to obtain a solution A; S2, weighing sodium ferrocyanide, and dissolving it in the second solvent to obtain solution B; S3, under a protective atmosphere, slowly dropwise adding the solution B into the solution A, reacting at room temperature, and then separating the solid and the liquid to obtain a solid product; S4, washing the solid product with water and / or ethanol, and then drying to obtain the positive electrode material.
7. An electrode material, characterized in that: The invention comprises the nickel-iron co-doped manganese-based Prussian blue positive electrode material as described in claim 1 or 2, or the nickel-iron co-doped manganese-based Prussian blue positive electrode material obtained by the preparation method as described in any one of claims 3-6.
8. An electrode, characterized in that: Comprising the electrode material according to claim 7.
9. An electrochemical energy storage device, characterized in that: Comprising the electrode according to claim 8.
Citation Information
Patent Citations
Gradient-structure Prussian white material and preparation method thereof, positive electrode material and sodium ion battery
CN115966689A